Why nations fail : the origins of power, prosperity and poverty - Acemoglu, Daron (Crown Publishers, 2013)
Why are some nations rich and others poor? Is it culture, the weather, geography? Perhaps ignorance of the right policies? Simply, no. None of these factors is either definitive or destiny. Daron Acemoglu and James Robinson conclusively show that it is ma